Christ, baptism, and the Lord's Supper: recovering the sacraments for evangelical worship - Vander Zee, Leonard J. (InterVarsity Press, 2004)
Winner of a Christianity Today 2005 Book Award!Baptism. The Lord's Supper. We recognize these church practices. But do we really grasp their meaning and place in Christian worship? Is our neglect of them hindering our communion with Christ? Are we missing the real drama of our salvation?Often the object of debate, the sacraments are likewise neglected and superficially understood. Leonard Vander Zee makes a compelling case that these problems can be overcome when we see the connection between Baptism and the Lord's Supper and the continuing ministry of Jesus Christ, the incarnate Word of God. Founding his discussion in biblical teaching reaching back to the creation narrative and forward to the teaching of Jesus and the apostle Paul, Vander Zee sees the Christ-centered celebration of these sacraments as essential to the renewal of the church. A reappropriation of Baptism and the Eucharist, especially in the evangelical church, holds great promise for healing the rift between the natural and the spiritual, the personal and social, the head and the heart, and between the body of believers and our Lord Jesus Christ who died for us and now lives to make intercessions for us. In Christ, Baptism and the Lord's Supper,Vander Zee not only opens up a Christ-centered approach to the sacraments but also provides guidance on the practical matters that face pastors and parishioners in the pursuit of a renewed and authentic Christian worship.